2023
DOI: 10.1007/s10499-023-01100-z
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein, vitamin E, and vitamin C levels on the growth and gonad development of hybrid male abalone (Haliotis fulgens ♂ × H. discus hannai ♀) by the orthogonal array design

Abstract: A natural feed of fresh seaweed and sixteen diets designed by L16 (43) orthogonal array were formulated to contain differentlevels of protein (200, 250 g, 300, 350 g/kg), α-Vitamin E (VE) (0, 0.1, 0.3, 0.5 g/kg) and Vitamin E (VC) (0, 0.5, 1, 1.5 g/kg) to evaluate the effects of dietary protein, VE, VC and their combination on growth and gonadal development of hybrid male abalone (Haliotis fulgens ×H. discus hannai ). Each diet was randomly assigned to triplicate groups of 18 abalones (34.27±2.93 g) that were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 98 publications
0
1
0
Order By: Relevance
“…This, in turn, might contribute to maintaining testosterone levels within a healthy range (Hidayatik et al, 2021). Similarly, in hybrid male abalone, Wang et al (2023) reported that dietary supplementation with Vit C and Vit E significantly increased the testosterone levels in the treated group compared to the control group.…”
Section: Effects Of Vitamin Supplementation On Testosteronementioning
confidence: 92%
“…This, in turn, might contribute to maintaining testosterone levels within a healthy range (Hidayatik et al, 2021). Similarly, in hybrid male abalone, Wang et al (2023) reported that dietary supplementation with Vit C and Vit E significantly increased the testosterone levels in the treated group compared to the control group.…”
Section: Effects Of Vitamin Supplementation On Testosteronementioning
confidence: 92%